The physiology of world-class sledge ice-hockey players - Sandbakk, O.; Bucher, S.; Skovereng, K.; Welde, B.; Ettema, G. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Sledge ice-hockey is a modified version of regular ice hockey targeting athletes with a physical disability, typically affecting the lower body. An aluminum sledge is used as an adaptive device and each player carries two sticks for puck handling and player movement. Thus, the players rely solely on their upper body to propel themselves across the ice surface. An ice sledge hockey game is performed as 3 periods of 15 minutes on a 60 x 30-m ice rink, characterized by a constant lternation between short dashes, stopping actions and circle moves leading to multiple changes of work load and intensity. In order to better understand the demands of worldclass sledge ice-hockey, the present study compared physical and technical abilities of world-class (WC) and national-class (NC) sledge ice-hockey players. METHODS: Six WC and six NC sledge ice-hockey players from the A and B Norwegian national team performed the following sport-specific tests on ice: 1) 30-m maximal sprint, 2) multiple sprints (eight 30-m sprints at 30 seconds intervals with active recovery) and 3) a time-trial technique test where the athletes controlled the puck through multiple turns. In the laboratory, a 3-min all out poling ergometer test was performed sitting in a modified poling machine to determine peak respiratory parameters, and 1 repetition maximal strength and peak power was assessed in the bench press (BPr), bench pull (BPu) and pull-down (PD) exercises. The athletes` training diaries over the last year were analyzed. RESULTS: WC players showed 10-13% faster times both for the single 30-m and throughout all eight sprints in the multiple sprint test, whereas the technique test was ~15% for the WC players (all P<0.05). In the ergometer test, WC players showed ~5% higher VO2peak in absolute values and significantly faster oxygen kinetics (both P<0.05). Furthermore, WC players showed 15-25% higher maximal strength and power in all exercises (all P<0.05). WC players trained ~15% higher total volume with 30% more sport-specific training on ice and twice as much low intensity endurance training (all P<0.05). CONCLUSIONS: The current results show that maximal sprint ability, upper-body maximal strength and power, and aerobic capacities differentiate world-class from national-class sledge ice-hockey players. It is therefore suggested that these physical capacities are important for reaching world-class level in this sport. In addition, also technical ability showed clear differences between performance levels. The current study also indicates that the combination of sport-specific training on ice and low-intensity endurance training are important in attaining an international level in sledge ice-hockey.